Net income, risk and business plan for Hauger farm - Hauger, Michael (Kansas State University, 2014)
The purpose of this thesis is to compare the net income and risk associated with custom farming, cash rent, and crop-share. This analysis will help provide insight on the best option for my 40 acres of farm land, which I recently was given from my mother. The 40 acres is located in Codington County, SD and has been previously in a corn, soybean, and wheat rotation. Another goal of the thesis is to create a business plan for Hauger Farm, which will lay out the activities involved for custom farming. The 40 acres will continue to be in a corn, soybean, and wheat rotation. A 12-year analysis was developed to determine the net income and risk associated with custom farming, cash rent, and crop-share. The analysis consisted of historical data from the past nine years while predicting the next three years. After creating the net income statement, the option providing the most income over the long-run was to have the land custom farmed. Custom farming also brought the most income variability or risk; while cash rent showed to have the lowest risk with the least variable income.
Keywords: Net Income; Cash rent; Farm land; Custom farming; Share rent; Business plan; Accounting (0272); Economics, Agricultural (0503); Management (0454)